Rules for nuns according to the Dharmaguptakavinaya: the discipline in four parts - Heirmann, Ann (Buddhist tradition series, 2002)
Complete annotated English translation of Chinese version of the Bhikṣuṇīvibhaṅga. - pt. 1. Introduction -- pt. 2. Translation -- pt. 3. Indices, glossaries, concordance, bibliography, Chinese text.